India’s biofuel blending policy presents serious trade-offs with land use, nitrogen emissions and food security - Chandan Kumar Jha; Miodrag Stevanović; Prantika Das; Jan Philipp Dietrich; Aline Mosnier; Alexander Popp; Ranjan Kumar Ghosh; Hermann Lotze-Campen (PLoS ONE, 2026)
This study examines the environmental and resource implications of India’s 20% ethanol blending mandate, with a focus on its effects on land use, water and fertilizer use, and greenhouse gas emissions. Using a global partial equilibrium model of the land-use sector, MAgPIE, we evaluate scenarios involving different feedstock combinations involving molasses and sugarcane juice. Results reveal that ethanol production from molasses exerts considerable pressure on natural resources due to the high land, water, and fertilizer demands of sugarcane. Conversely, ethanol derived from sugarcane juice proves to be a more sustainable option, requiring less water and fertilizer while generating lower greenhouse gas emissions. Nevertheless, all scenarios present challenges related to food security, through increases in food prices, and resource competition. Sensitivity analysis shows that limited technological progress or constrained trade amplify domestic land, water, and emission burdens. Our findings provide directly usable evidence for designing India’s biofuel roadmap. They can inform (a) the choice of feedstock-mix for achieving blending targets with lower land, water, and nitrogen footprints (b) complementary policies on fertilizer management, irrigation efficiency, and trade; and (c) the timing and scale-up of diversified and second-generation feedstocks. Overall, the study highlights that careful management of feedstock portfolios and supporting agricultural policies is essential for aligning India’s ethanol expansion with long-term climate, food security, and resource sustainability goals.